Ventricular septal defect: early against late surgical repair. Issue 1 (1st January 2016) - Siddiqui, Waqas J.; Iyer, Praneet; Amba, Samridhi; Muddassir, Salman; Cheboterav, Oleg
Abstract : Ventricular septal defect (VSD) is a rare complication of right ventricular infarction (RVI) which is associated with significant mortality, if not treated appropriately. It typically occurs within the first 10–14 days after myocardial infarction. Surgical repair has been shown to reduce in-hospital mortality from 90% to 33–45%. Early surgical VSD repair has also been associated with high 30-day operative mortality of 34–37%. Furthermore, after an acute MI the friable myocardium enhances the risk of recurrent VSD with early surgical repair. We present a case of a middle-aged woman who developed VSD after an RVI. Her surgical repair was delayed by 2 weeks due to development of Staphylococcus aureus bacteremia. During this period, she was managed medically and later on underwent percutaneous repair with an amplatzer VSD occluder device. Keeping this patient encounter in mind, we would like to emphasize on the limited recommendations available for early against late surgical repair of VSD.